Language Prejudice and Language Structure: On Missing and Emerging Conjunctions in Libras and Other Sign Languages - Rodrigues, Angélica [UNESP]; Pfau, Roland (Springer Nature, 2023)
Sign languages, just like many indigenous languages, have traditionally been subject to language prejudice and suppression, based in no small part on invalid claims about their structural complexity. In this chapter, we aim to contribute to the discussion on language prejudice by broadening the scope to include deaf communities and their sign languages. We review and reject claims according to which languages can be classified as “primitive” or “evolved” based on the absence of certain grammatical categories. One such grammatical category are conjunctions, and we investigate in some detail their absence or presence in sign languages. We present examples from various sign languages which show that – just as in spoken languages – conjunctions may emerge through diachronic processes of borrowing and grammaticalization. Focusing on data from Brazilian Sign Language, we then demonstrate that both these processes are at play in the language and that manual conjunctions marking disjunctive, adversative, conditional, and causal relations have entered the lexicon. Our hope is that these findings will contribute – albeit modestly – to the status of Brazilian Sign Language.
Keywords: Borrowing; Conjunction; Grammaticalization; Language prejudice; Sign language